Systematisation of seismic retrofitting in vernacular architecture - Lima, A. (2015)
This paper aims to identify and to systematize the data obtained during the working process of the research project 'SEISMIC-V –Vernacular Seismic Culture in Portugal' in terms of seismic- retrofitting elements earthquake -resistant reinforcement implemented in vernacular buildings. The data will be distinguished based on the structural seismic strengthening and according to the following criteria: strengthening elements, perimeter seismic-resistant elements, arches reinforcing elements, and combined reinforcing elements.